KEBIJAKAN FORMULASI GRATIFIKASI SEKSUAL TERHADAP PENYELENGGARA NEGARA - Handrawan Handrawan; Deity Yuningsih; Ahmad Firman Tarta (Lakidende Law Review, 2022)
Sexual gratification in Indonesia can be punished because the practice of sexual gratification can be equated with the practice of corruption because it is classified as a latent crime even though it is difficult to prove but as long as the elements of the perpetrator are people who give bribes to officials and their sexual servants as well as during transactions and services. If the sexual relationship has a connection or has something to do with the authority and position given to an official or state administrator, that person can be charged with regulations related to how the facts of the trial are developed. In addition, the phrase element in Article 12B regarding "other facilities" can be interpreted with a systematic and authentic interpretation which can be interpreted as sexual. In addition, in several countries such as Singapore and America, perpetrators of sexual gratification can be criminally charged because there is already a law that regulates it. Therefore, even Indonesia can apply this concept clearly in its laws.